2011
DOI: 10.1007/s11469-011-9318-5
|View full text |Cite
|
Sign up to set email alerts
|

Internet Gaming Addiction: A Systematic Review of Empirical Research

Abstract: The activity of play has been ever present in human history and the Internet has emerged as a playground increasingly populated by gamers. Research suggests that a minority of Internet game players experience symptoms traditionally associated with substance-related addictions, including mood modification, tolerance and salience.Because the current scientific knowledge of Internet gaming addiction is copious in scope and appears relatively complex, this literature review attempts to reduce this confusion by pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

39
636
2
66

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 816 publications
(743 citation statements)
references
References 97 publications
(260 reference statements)
39
636
2
66
Order By: Relevance
“…Indeed, many participants reported that gaming was a way of living. This is not surprising as many studies have noted that such games attract millions of people all over the world (e.g., Chappell, Eatough, Davies & Griffiths, 2006;Kuss & Griffiths, 2012a;Yee, 2005). The recent development of MMORPGs has created a new experience for gamers (Smyth, 2007), that has generated an increase of research in this field.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Indeed, many participants reported that gaming was a way of living. This is not surprising as many studies have noted that such games attract millions of people all over the world (e.g., Chappell, Eatough, Davies & Griffiths, 2006;Kuss & Griffiths, 2012a;Yee, 2005). The recent development of MMORPGs has created a new experience for gamers (Smyth, 2007), that has generated an increase of research in this field.…”
Section: Discussionmentioning
confidence: 93%
“…Frostling-Henningsson, 2009) and gambling (Wood & Griffiths, 2002) and the feelings that are triggered by gambling (Griffiths, 1991a;2011a) and video gaming (Kuss & Griffiths, 2012a;2012b).…”
Section: Gamblingmentioning
confidence: 99%
See 3 more Smart Citations